Determination of the Shortest Distribution Routes to Minimize Fuel Consumption and CO2 Emission Using Sweep and Clarke & Wright Saving Algorithms - Riski Arifian; Farida Pulansari (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2023)
Nowadays, one of the areas in the field of vehicle routing problems that have received a lot of attention is Green Vehicle Routing Problem (GVRP). GVRP aims to harmonize the financial aspects and environmental concerns while routing vehicles. This research takes a case study at PT. LISA CONCRETE INDONESIA is a company engaged in the concrete industry with various precast concrete products. One of the company's main products is U-Gutter which recorded the highest sales in the company in 2022 with sales of 14,000 tons. According to the high demand for these products, it can be confirmed that the distribution activities to customers are also increased which have a negative impact on the environment. In this research, classical heuristics namely Sweep and Clark & Wright saving algorithm are used. Both of these methods will be implemented using Microsoft Excel software to determine the shortest distribution routes to deliver products to customers in PT. LISA CONCRETE INDONESIA and also to minimize fuel consumption and CO2 emission. The result shows that Clark & Wright saving algorithm is 11,49% better than the Sweep algorithm and also 43,23% better than the company/existing method to minimize fuel consumption and CO2 emission.